Forms of abuse and its relationship to social and psychological adaptation among students in Jordan - Alanasweh, Ali Mosa Mohammad; Banat, Suhaila Mahmood Saleh (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the forms of abuse and its relationship to the social and psychological adaptation among students in Jordan, and identify the most common forms of abuse of recognized by students, and to identify the level of psychological and social adaptation among students. This study adopted the descriptive correlation approach, and the sample of the study consisted of (91) students of the fifth and sixth grades who study in public schools in the Directorate education of the salt and are exposed to types of abuse To achieve from (11/5-9/6/202) To the objectives of the study, two main scales were relied upon to gather the necessary information (the measure of forms of abuse, the psychosocial adjustment measure). The study found that student abuse came at a high level for all its forms, except for physical abuse, which came at a medium level, and sexual abuse at a low level. The results showed that the students ’level of social and psychological adjustment was low, and the results showed a statistically significant negative relationship between the forms of abuse as perceived by students and the level of social and psychological adjustment. The researcher recommended the need to work on establishing centers for family and school guidance in all regions, providing courses for parents, teachers in how to deal with students and providing support, love and guidance necessary for them.